Meneladani Akhlak Wanita dari Akhlak Para Istri Nabi (Analisis Surat Al-Ahzab Ayat 28-35 dalam Kitab Tafsir Al- Azhar Karya Buya Hamka) - Widiani Hidayati; Faisal Saleh (EL-TARBAWI, 2021)
This paper intends to discuss how the morals of the Prophet's wives, whichare summarized in Surah Al-Ahzab verses 28-35, used as directions,references, and instructions for women. The wives of the Prophet are themothers of religious people so that it should be used as an example byMuslims, especially for women. In analyzing Surat Al-Ahzab verses 28-35,the writer uses the library research approach, with the primary data sourceis Buya Hamka's book of Tafsir Al-Azhar. and for the secondary data, thewriter uses various books and journals that are relevant with the topic. Thispaper concluded that according to Buya Hamka interpretation, the moralsordered by Allah SWT to women in Surat Al-Ahzab verses 28-35, is tochoose the afterlife over the temporary world or implementing simple life,not to commit heinous acts towards others, such as condemning, cursing atpeople, stealing, slandering, because it can drop a woman's honor, speakingwell, politely, firmly, not weak and flirtatious, staying at home, not overlymade up and dressed up, worshiping (reading the Koran, giving charity,Fasting, Dhikr) with khusyu, and clear from all the qualities that defile theheart (envy, arrogance, envy, and greed).Keyword: Morality, Tafsir, Character Education, Buya Hamka